MODELLING OF RSG-GAS HEAT EXCHANGER FOR STEADY-STATE SIMULATION - Andi S Ekariansyah (SIGMA EPSILON - Buletin Ilmiah Teknologi Keselamatan Reaktor Nuklir, 2018)
MODELLING OF RSG-GAS HEAT EXCHANGER FOR STEADY-STATE SIMULATION. The multipurposes reactor G.A Siwabessy (RSG-GAS) is a open pool, water cooled reactor with plate type fuel elements having thermal power of 30 MWt. Its design has been a subject for research in term of its safety against postulated design basis accident. For the purpose of safety analysis, its complete design have been modelled using various thermalhydraulic code, which has to be validated for the steady-state condition. The model generated so far did not include the model of the heat exchanger as it is designed and described in the RSG-GAS design specification. Therefore the purpose of this research is to obtain a heat exchanger model as realistic as possible using the RELAP5/ SCDAP/Mod3.4 code. From the generated model, the performace of the heat exchanger design will be evaluated to analyze its effect on the steady-state simulation during RSG-GAS full power. The simulation results show that the performance of the obtained heat exchanger model has been validated with the design specifications to remove the core heat during the full power simulation. On that condition, the inlet secondary temperature and loss coefficient plays important role in taking the inlet and outlet primary temperature to be close with the experimental data and other RSG-GAS model.Keywords: RSG-GAS, heat exchanger model, RELAP5, steady state simulation, performance